Long-range dependence in returns and volatility of Central European Stock indices - Ladislav Krištoufek (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In the paper, we research on the presence of long-range dependence in returns and volatility of BUX, PX and WIG between years 1997 and 2009 with use of classical and modified rescaled range. Moving block bootstrap with pre-whitening and postblackening is used for the construction of confidence intervals for the hypothesis testing. We show that there is no significant long-range dependence in returns of all examined indices. However, significant long-range dependence is detected in volatility of all three indices. The results for returns are contradictory with several studies which claim that developing markets are persistent. However, majority of these studies either do not use the confidence intervals at all or only the ones based on standard normal distribution. Therefore, the results of such studies should be reexamined and reinterpreted.
Keywords: C4; C5; G15; 330; long-range dependence; rescaled range; modified rescaled range; bootstrapping; Zeitreihenanalyse; Statistische Methode; Kapitaleinkommen; Volatilität; Aktienindex; Ungarn; Tschechische Republik; Polen